3D Modelling of Fluctuation Effects in Highly Scaled VLSI Devices. Issue 1 (2001) - Linton, Thomas D.; Yu, Shaofeng; Shaheed, Reaz
Abstract : Fluctuation effects are becoming important in advanced VLSI devices because of their increasing impact on circuit performance and chip yields. Accurate modelling of these effects generally requires full 3D simulation, which is used here to analyse four of the primary such effects. Polysilicon line edge roughness causes excess device leakage, which can be reduced at the cost of decreased performance. Phase-shift mask defects can reduce current drive and increase capacitance. Random dopant fluctuation, which causes variation in threshold voltage, is evaluated for three technology generations and it is shown that proper tip scaling can reduce these variations. Finally, a study of alpha particle strikes evaluates the effectiveness of SOI in improving soft error reliability.